Similar Blood Glucose Pattern with Highest Peak at Minute 45 on Oral Glucose Tolerance Test Despite Higher Fasting Insulin and Insulin Resistance in Healthy Obese than Non-Obese Subject - Made Ratna Saraswati; Ida Bagus Aditya Nugraha; Ketut Suastika (Interna Publishing, 2022)
Background: Obesity increase the risk for type 2 diabetes through induction of insulin resistance. Diagnosis of diabetes were based on blood glucose level. However, insulin resistance may had happened far before diagnosis itself. This study aimed to compare fasting insulin level, insulin resistance, and blood glucose pattern during oral glucose load in healthy obese and non-obese subject. Methods: This semi-experimental study was conducted at Department of Internal Medicine, Sanglah Hospital, Denpasar. Sixteen subjects in each obese and non-obese group were matched by age and sex. Obesity was defined based on body mass index (BMI) of ≥25kg/m2 and waist circumference (WC) ≥80cm (female) or ≥90cm (male). The non-obese group was defined by BMI of 18-25kg/m2 and WC <80cm (female) or <90cm (male). Fasting insulin level and blood glucose was measured at minute 0, 15, 30, 45, 60, 75, 90, 120 after glucose load of 75 grams. Insulin resistance was calculated based on homeostasis model assessment of insulin resistance (HOMA-IR) with the following formula: HOMA-IR = (FPI×FPG)/22.5. Normal glucose tolerance (NGT) and impaired glucose tolerance (IGT) subject was defined by American Diabetes Association (ADA) criteria. Results: Fasting insulin level in obese subjects was higher than non-obese subjects with median 12.75 (range 3.70 - 41.30) vs 3.80 (1.80 - 36.80) µU/mL, p=0.041. HOMA IR was also higher in obese subjects compared to non-obese subjects: 2.45 (0.70 - 8.00) vs 0.80 (0.40 - 8.50), p=0.001. Fasting insulin level was correlated with BMI (r=0.559, p=0.001) and WC (r=0.633, p<0.001). A significant correlation was also detected between HOMA IR with BMI (r=0.528, p=0.002) and WC (r=0.600, p<0.001). Blood glucose pattern in four groups: obese IGT, obese NGT, non-obese IGT, and non-obese NGT, were typically similar, in particular two peaks of blood glucose. The first peak was the highest blood glucose, shown in minute 45 in both obese and non-obese subjects. The second peak was lower than the first peak, found in minute 75 among NGT and minute 90 among IGT subject. Blood glucose level for each measurement point was consistently higher in obese than non-obese subjects. Conclusion: Fasting insulin level and HOMA-IR were higher in obese than in non-obese subjects. BMI and WC were significantly correlated with fasting insulin level and HOMA IR, so that high BMI and WC can be an earlier clinical sign of insulin resistance and prediabetes. Pattern of blood glucose level after oral glucose load were similar with two peaks, and blood glucose consistently higher in obese compared to non-obese subjects. The highest peak of blood glucose, shown in minute 45 in both obese and non-obese subjects.